2021
DOI: 10.1038/s41467-021-23343-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel symmetrical bifacial flexible CZTSSe thin film solar cells for indoor photovoltaic applications

Abstract: Environment-friendly flexible Cu2ZnSn(S,Se)4 (CZTSSe) solar cells show great potentials for indoor photovoltaic market. Indoor lighting is weak and multi-directional, thus the researches of photovoltaic device structures, techniques and performances face new challenges. Here, we design symmetrical bifacial CZTSSe solar cells on flexible Mo-foil substrate to efficiently harvest the indoor energy. Such devices are fabricated by double-sided deposition techniques to ensure bifacial consistency and save cost. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 35 publications
0
53
0
Order By: Relevance
“…to the convex bending in a bifacial flexible CZTSSe device was more significant than that at the surface subjected to the concave bending as the crystalline structure was damaged. 58 After 1000 bending cycles, the decrease in the PCE was -6.82% and -9.13% for concave and convex bending, respectively, showing that more than 90% of the PCE was maintained after the bending test. Jeong et al also demonstrated that flexible CZTSSe thin-film solar cells using Mo metal foil maintained over 90% of their initial PCE after the bending test with a bending radius of more than 3 mm.…”
Section: Loss Mechanism Of Open-circuit Voltage Under Mechanical Stressmentioning
confidence: 89%
“…to the convex bending in a bifacial flexible CZTSSe device was more significant than that at the surface subjected to the concave bending as the crystalline structure was damaged. 58 After 1000 bending cycles, the decrease in the PCE was -6.82% and -9.13% for concave and convex bending, respectively, showing that more than 90% of the PCE was maintained after the bending test. Jeong et al also demonstrated that flexible CZTSSe thin-film solar cells using Mo metal foil maintained over 90% of their initial PCE after the bending test with a bending radius of more than 3 mm.…”
Section: Loss Mechanism Of Open-circuit Voltage Under Mechanical Stressmentioning
confidence: 89%
“…Kesterite Cu 2 ZnSn­(S,Se) 4 (CZTSSe) is a potential absorber material to replace a similarly structured chalcopyrite counterpart Cu­(In,Ga)­Se 2 (CIGS) due to its rich elemental composition, excellent optoelectronic properties, tunable band gaps, and higher theoretical efficiency. Flexible CZTSSe solar cells have great application potentials such as in the field of building-integrated photovoltaic, portable equipment and indoor photovoltaic owing to their nontoxicity, excellent mechanical flexibility, and high stability. Mo foil is a good flexible substrate for CZTSSe solar cells . It can reduce process cost without sputtering the Mo layer in the device preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Solar photovoltaic (PV) energy accounts for only a small part of global electricity production, although it has the potential to meet the global energy needs by several folds through the use of currently available technologies [1]. High costs and low power conversion efficiency (PCE) have been the major bottlenecks in the development of solar PV power to become a primary source of energy, while engineering the characteristics of PVs is required to open the way for pioneer and niche applications [2][3][4]. To deal with this situation, the development of emerging PV technologies is currently investigated, promising a low levelized cost of electricity (LCOE), additionally offering a plethora of advantages and unique characteristics [5].…”
Section: Introductionmentioning
confidence: 99%
“…The hysteretic phenomena in the electrical characteristics of both types of devices were also investigated since they are a critical issue related to the performance and stability of PSCs. The hysteresis index (HI) was calculated using Equation (3).…”
mentioning
confidence: 99%